Impact of fatigue on the position of the release arm and shoulder girdle over a longer shooting distance for an elite basketball player - Erculj, F.; Supej, M. (The Journal of Strength and Conditioning Research, 2009)
The purpose of this case study is to establish how a gradual increase in fatigue affects the position of the arms and shoulders during a long shot in a basketball game. For this purpose, Primož Brezec, an elite National Basketball Association player, performed a total of 7 series of 20 shots from a distance of 7.24 m. The subject performed a special basketball motor task between individual series' of shots. The fatigue gradually increased with each motor task, and in the meantime, the subject's heart rate (HR) and blood lactate concentration (LA) were measured. The height of each jump during the shot at the basket was measured, and all shots were recorded using a system of 3 digital cameras operating at a frequency of 50 Hz. Thereafter, a kinematic analysis was applied to calculate the height of the shoulder and wrist of the release arm, as well as the elbow and upper arm angles, with regard to the vertical line. The study results reveal statistically significant differences (p < 0.05) between the series of throws in all measured variables. The heights of the shoulder axis and of the wrist both decrease with growing fatigue. This is particularly apparent in the last series, i.e., in the conditions of maximum fatigue (HR = 96% HRpeak; LA = 9.7 mmol/L). Both measured angles decrease drastically in the last series of shots. The results of the study clearly demonstrate changes in the shooting technique as a consequence of moderate and, in particular, heavy fatigue. The findings also suggest the need for basketball coaches and basketball conditioning coaches to include moderate- and high-intensity exercise in their shooting practice sessions.